“Milk is Milk”: Marketing Milk in Ontario and the Origins of Supply Management - Nurse-Gupta, Jodey (Journal of the Canadian Historical Association / Revue de la Société historique du Canada, 2017)
Neoliberal policies dominate the discourse on international agricultural trade. Canada’s system of supply management in dairy, eggs, and poultry, however, remains intact despite being a polarizing topic both nationally and abroad. To better understand the ideological rift that exists between those who support and oppose the system, this article examines the creation of the Ontario Milk Marketing Board (OMMB) in 1965, which introduced fairer producer pricing and production discipline through the establishment of milk pools. Before the OMMB was created, chronic oversupplies of milk resulted in devastatingly low milk prices paid to farmers, which caused significant distress in the dairy community. This article examines the divisions between industry stakeholders during the implementation of the milk marketing board in order to better understand why some saw the board’s plans as rational and fair, while others believed OMMB policies infringed on their freedom and retarded the rationalization of the Ontario dairy industry.